The Priesthood in Ancient Israel - Leuchter, Mark (Biblical theology bulletin, 2010)
The priesthood in ancient Israel developed through the confluence of different social forces over a broad spectrum of time. The social, textual, mythic and political concerns of Israel’s priestly groups are evident throughout the biblical record, and reveal the depth of influence the priesthood exerted not only on the formation of the Bible but on the growth of Israelite religion into early Judaism.